Helping the intellectually impaired: Steenkamp, E & Steenkamp W (1992) The intellectually handicapped child: A manual for parents, teachers and related professions. Durban: Butterworths. - Uys, Leanna (PINS-Psychology in Society, 2026)
The intellectually handicapped child is the second edition of this book, whose first edition was titled The mentally handicapped child. The change in title is briefly commented on in the introduction, where the authors point out that "intellectually" handicapped is a more specific term, and therefore more appropriate to the group of children they are writing about. This is indeed a welcome change, especially for consumer groups, who are very conscious of the stigma attached to the word "mental". Although the authors also refer to the term "impaired" rather than "handicapped", they prefer not to use this terminology. This is unfortunate, since it is the internationally accepted terminology also accepted by "Disabled People South Africa (DPSA)".